2013
DOI: 10.1177/0956797612469537
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Training Alters Altruism and Neural Responses to Suffering

Abstract: Compassion is a key motivator of altruistic behavior, but little is known about individuals’ capacity to cultivate compassion through training. We examined whether compassion may be systematically trained by testing whether (i) short-term compassion training increases altruistic behavior, and (ii) individual differences in altruism are associated with training-induced changes in neural responses to suffering. In healthy young adults, we found that compassion training increased altruistic redistribution of fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
406
1
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 491 publications
(435 citation statements)
references
References 39 publications
13
406
1
15
Order By: Relevance
“…This could sometimes even lead to them violating socially accepted norms (28) as they are working towards meeting impersonal organisational targets (29). However, compassion can be cultivated through training that increases altruistic behaviour in compassion trainees via neural mechanisms controlling emotion prompting them to respond to rather than avoid suffering of others (30). The proposal to incentivise compassion proposed by the UK government to address the failures of care (3) will not succeed if it is not geared to promote prosocial behaviour but rather to implement target measures that have induced the failure of compassion in the first place.…”
Section: The Question That Arises Is How Can We Live Up To the Demandmentioning
confidence: 99%
“…This could sometimes even lead to them violating socially accepted norms (28) as they are working towards meeting impersonal organisational targets (29). However, compassion can be cultivated through training that increases altruistic behaviour in compassion trainees via neural mechanisms controlling emotion prompting them to respond to rather than avoid suffering of others (30). The proposal to incentivise compassion proposed by the UK government to address the failures of care (3) will not succeed if it is not geared to promote prosocial behaviour but rather to implement target measures that have induced the failure of compassion in the first place.…”
Section: The Question That Arises Is How Can We Live Up To the Demandmentioning
confidence: 99%
“…Of the 54 papers that underwent a full-text review, the five most common reasons for exclusion were that the study: (i) featured a single-dose adapted LKM or CM experimental test rather than training as part of a program of psychotherapy (e.g., Barnhofer, Chittka, Nightingale, Visser, & Crane, 2010;Crane, Jandric, Barnhofer, & Williams, 2010;Engström, & Söderfeldt, 2010;Feldman, Greeson, & Senville, 2010;Hutcherson et al, 2008;Lee et al, 2012;Logie & Frewen, 2014), (ii) utilized an intervention integrating lovingkindness and/or compassion techniques that was not based on meditation (e.g., Gilbert & Procter, 2006;Leiberg et al, 2011;Mayhew & Gilbert, 2008;Oman, Thoresen, & Hedberg, 2010), (iii) was not designed to explicitly assess changes in the symptom severity of DSM-IV-TR Axis I disorders in clinical samples and/or known concomitants thereof in subclinical/healthy samples (e.g., Condon, Desbordes, Miller, & DeSteno, 2013;Hunsinger, Livingston, & Isbell, 2013;Mascaro, Rilling, Negi, & Raison, 2013b;May et al, 2011;Weng et al, 2013), (iv) was primarily based on self-compassion techniques (e.g., Albertson, Neff, & Dill-Shackleford, 2014;Neff & Germer, 2013;Shapira, & Mongraina, 2010), or (v) was not published in a peer-reviewed journal (e.g., Humphrey, 1999;Kleinman, 2011;Law, 2012;Templeton, 2007;Weibel, 2008).…”
Section: Primary Reasons For Exclusionmentioning
confidence: 99%
“…Similarly, Weng et al (2013) showed that LKM increased altruistic redistribution of funds to a 'victim' figure encountered outside the training context. If LKM increases prosociality, inter-group processes would appear to be an area of human life likely to benefit from such an effect.…”
mentioning
confidence: 99%